Contribution to the knowledge of Agrypninae (Coleoptera: Elateridae) with description of new species and new records from Pakistan - Akhter, Muhammad Atique; Drumont, Alain; Rizvi, Syed Anser; Ahmed, Zubair (Zootaxa, 2012)
Thirty-two species, belonging to ten genera are listed in this work, including eight species newly recorded from the coun-try. The study is based upon material collected in Pakistan between 2004–2010. The genus Cryptalaus Ohira is recordedfrom Pakistan for the first time. Two species Cryptalaus tamargrahensis sp. n. and Agrypnus dadarensis sp. n. are de-scribed as new and a key to the Pakistani species of the genera Agrypnus Eschscholtz, Lanelater Arnett, Drasterius Eschscholtz and Heteroderes Latreille are provided.